MORAL TOKOH UTAMA DALAM NOVEL ALIF KARYA TAUFIQURRAHMAN AL-AZIZY - Wira Widyas Tuty; Edi Suyanto; Eka Sofia Agustina (FKIP Universitas Lampung, 2013)
The problem of this research is how are the moral aspects of the main character in the novel Alif written by Taufiqurrahman Al-Azizy. The aim of this research is to describe the moral aspects of the main character in the novel Alif written by Taufiqurrahman Al-Azizy and the worthiness as a material lesson of literature in SMA. The research method used is qualitative descriptive method. The data resource used is from the novel Alif written by Taufiqurrahman Al-Azizy. Collecting technique and data analysis used is text analysis. Based on the data analysis result found , the moral aspects of the main character in novel Alif written by Taufiqurrahman Al-Azizy include honesty, authentic values, the willingness to take responsibility, undependability, courage, modesty , realistic and criticality. Novel Alif written by Taufiqurrahman Al-Azizy is worthy to be used as a material lesson alternative for students in SMA.Masalah penelitian ini adalah bagaimanakah aspek moral tokoh utama dalam novel Alif karya Taufiqurrahman Al-Azizy. Tujuan penelitian ini untuk mendeskripsikan aspek moral tokoh utama dalam novel Alif karya Taufiqurrahman Al-Azizy dan kelayakannya sebagai bahan ajar sastra di SMA. Metode penelitian yang digunakan adalah metode deskriptif kualitatif. Sumber data dalam penelitian ini adalah novel Alif karya Taufiqurrahman Al-Azizy. Teknik pengumpulan dan analisis data yang digunakan adalah analisis teks. Berdasarkan hasil analisis data ditemukan aspek moral tokoh utama dalam novel Alif karya Taufiqurrahman Al-Azizy meliputi kejujuran, nilai-nilai otentik, kesediaan untuk bertanggung jawab, kemandirian moral, keberanian moral, kerendahan hati, realistik dan kritis. Novel Alif karya Taufiqurrahman Al-Azizy layak dijadikan sebagai alternatif bahan ajar siswa di SMA.Kata kunci: kelayakan, moral, tokoh utama.